2022
DOI: 10.1523/eneuro.0287-21.2022
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and Potential Significance of Spontaneous Activity in the Habenula

Abstract: The habenula is an evolutionarily conserved structure of the vertebrate brain that is essential for behavioural flexibility and mood control. It is spontaneously active and is able to access diverse states when the animal is exposed to sensory stimuli.Here we investigate the dynamics of habenula spontaneous activity, to gain insight into how sensitivity is optimized. Twophoton calcium imaging was performed in resting zebrafish larvae at single cell resolution. An analysis of avalanches of inferred spikes sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…1g ). This branching number is significant because previous work has found that networks with a branching number of closely reproduced the in vivo dynamics of cortical spiking across many different species 32 , 33 , making this a physiologically plausible parameter value. Placing synapses suboptimality led to proportionally lower dipole correlation, revealing that subcritical dynamics can still drive coherent dipoles with suboptimal synapse placement (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1g ). This branching number is significant because previous work has found that networks with a branching number of closely reproduced the in vivo dynamics of cortical spiking across many different species 32 , 33 , making this a physiologically plausible parameter value. Placing synapses suboptimality led to proportionally lower dipole correlation, revealing that subcritical dynamics can still drive coherent dipoles with suboptimal synapse placement (Fig.…”
Section: Resultsmentioning
confidence: 99%